Pengasuhan Demokratis dalam Pengembangan Sosial Emosional Anak Usia Dini di Tempat Penitipan Anak Ibunda Ponorogo - Suci Midsyahri Azizah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
Early childhood grows and develops so fast one of which is social development. Child Care Center (TPA) is one way for children to continue to get good education and care as long as parents are busy working. This study uses a research approach that is qualitative with the type of research that is a case study. This research was conducted in Ibunda Child Care Center Jln. Sumatra Banyudono Ponorogo, using data collection techniques namely by observation, interview, documentation and triangulation techniques. Based on the analysis of the data it can be concluded that, firstly, the parenting strategies carried out in the Ibunda's Day Care Center use democratic parenting by promoting children's social emotion based on children's enthusiasm, feeling happy and happy and not giving rules that curb children's expression. The rules that are made in TPA are to control the attitudes and traits for the purpose of forming a better character. Secondly, the implications of the pattern of democratic care in the Ibunda's Child Care Center have a significant positive effect. The children who are entrusted to the TPA, become more confident, independent, and can be more friendly and have good self-control.